The Effect of Service Quality on Community Satisfaction of Public Service Mall Users in Sidoarjo Regency - Wahyu Febrianto; Sri Wibawani (Universitas Medan Area, 2022)
This article aims to empirically test the influence of service quality on the satisfaction of the community users of Sidoarjo Regency Public Service Mall. The problem is focused on the quality of service contained in the Sidoarjo Regency Public Service Mall. To approach this problem, theories from Zeithaml, Berry, and Parasuraman are used about 5 (five) indicators of service quality, including tangible, reliability, responsiveness, assurance, and empathy that are analyzed quantitatively. The data analysis techniques applied in this study use instrument validity and reliability tests, variable descriptive statistical analysis tests, inferential statistical analysis tests, simple linear regression analysis tests, determination coefficient (R2) tests, t statistical tests. This study shows that the effect of service quality on the satisfaction of the community of users of the Sidoarjo Regency Public Service Mall gives a significance value of 0,000 and the value is smaller than 0.05. The data showed that the quality of service had a positive effect on community satisfaction, which made Ha accepted and Ho rejected. The results also showed an R Square value of 0.171 or 17.10%. This explains that the contribution of service quality related to the community satisfaction variable is worth 17.10%. While the rest of the calculation is worth 82.90% due to the influence of other factors that are not included in this study.